2020
DOI: 10.1111/rda.13842
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate models for estimating jackass semen production and quality

Abstract: The purpose of this study was to analyse the effects of season, age, gonad and accessory sex glands on semen characteristics of jackass and to construct multivariate regression models to predict semen quality. In autumn, spring and summer, semen characteristics of 30 sexually mature donkeys (1,014 ejaculations) were analysed to investigate the effect of seasons on semen quality, and gonad and accessory sex gland parameters of 12 jackasses were measured immediately after ejaculation by ultrasonography to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
(55 reference statements)
1
4
0
Order By: Relevance
“…Additionally, azoospermia stages have been described in donkeys due to plugged ampullae causing total ampullae obstruction (Segabinazzi et al 2018) or after immunocastration procedures (Rocha et al 2018), but also may be physiologically mediated by undifferentiated embryonic cell transcription factor 1 (UTF 1) and deleted in azoospermia-like (DAZL) expression in donkey testis (Lee et al 2017;Choi et al 2020) and has been suggested to be an effect derived from ageing (Liu et al 2021) which was supported by our results as shown in Figure 3. Figure 8 also describe a decrease in total spermatozoa motility which is concomitant with the azoospermia stage detected in Figure 3.…”
Section: Doradosupporting
confidence: 84%
“…Additionally, azoospermia stages have been described in donkeys due to plugged ampullae causing total ampullae obstruction (Segabinazzi et al 2018) or after immunocastration procedures (Rocha et al 2018), but also may be physiologically mediated by undifferentiated embryonic cell transcription factor 1 (UTF 1) and deleted in azoospermia-like (DAZL) expression in donkey testis (Lee et al 2017;Choi et al 2020) and has been suggested to be an effect derived from ageing (Liu et al 2021) which was supported by our results as shown in Figure 3. Figure 8 also describe a decrease in total spermatozoa motility which is concomitant with the azoospermia stage detected in Figure 3.…”
Section: Doradosupporting
confidence: 84%
“…Based on our previous studies, at these latitudes, the TSN should not vary significantly over the seasons even if, in the winter months, the reduction in daylight hours leads to a reduction in testosterone concentrations, resulting in a slight decrease in testicular volume and sperm concentration [18,23]. Liu et al [1] also reported no significant changes in testicular volume and sperm concentration throughout the year.…”
Section: Discussionmentioning
confidence: 89%
“…Conservation and breeding programs should involve healthy, in line with standards, and highly fertile subjects. A method that has been used in the livestock sector for estimating fertility is the evaluation of testicular size and its correlation with daily sperm production [1]. Recently, such studies have also been carried out on the donkey population, both in breeds bred for commercial purposes, such as the Dezhou donkey [2], and in those at risk of extinction, such as the Ragusano donkey [15] and Miranda's donkey [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations